Upregulation of lncRNA LINC00460 Facilitates GC Progression through Epigenetically Silencing CCNG2 by EZH2/LSD1 and Indicates Poor Outcomes - Yang, Jiebin (Mol Ther Nucleic Acids, 2020)
Non-protein-coding functional elements in the human genome in the postgenomic biology field have been drawing great attention in recent years. Thousands of long non-coding RNAs (lncRNAs) have been found to be expressed in various tumors. Yet only a small proportion of these lncRNAs have been well characterized. We have demonstrated that LINC00460 could affect cell proliferation through epigenetic regulation of KLF2 and CUL4A in human colorectal cancer. However, the clinical significance and biological role of LINC00460 in gastric cancer (GC) remain largely unknown. In this research, we discovered that LINC00460 is remarkably upregulated in GC tissues compared to the non-tumor tissues. Additionally, LINC00460 served as an independent prognostic marker in GC. Functionally, proliferation of GC cells could be regulated by LINC00460 both in vitro and in vivo. RNA sequencing (RNA-seq) analysis for the whole transcriptome indicated that LINC00460 may serve as a key regulatory factor in the tumorigenesis of GC. What’s more, the biological function of LINC00460 was mediated, to certain extent, by the direct interaction with enhancer of zeste homolog 2 (EZH2) and lysine (K)-specific demethylase 1A (LSD1) proteins. Further analyses indicated that LINC00460 promoted GC proliferation at least partly through the downregulation of tumor suppressor-gene Cyclin G2 (CCNG2), which is mediated by EZH2 and LSD1. In conclusion, our results suggested that LINC00460 acted as an oncogene in GC to inhibit the expression of CCNG2 at least partly by binding with EZH2 and LSD1. Our study could provide additional insights into the development of novel target therapeutic methods for GC.